Endometriosis Seen at Diagnostic Laparoscopy for Women with Infertility - Joseph Ifeanyichukwu Ikechebelu; George Uchenna Eleje; Chidimma Donatus Okafor; Abdulhakeem Olajide Akintobi (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2015)
Objective: To determine the prevalence and laparoscopic features of endometriosis in women investigated for infertility using laparoscopy and dye test. Methods: This was a retrospective survey at Life Institute for Endoscopy, Limited, Nnewi, Nigeria between January 2006 and December 2008. Data was collected with a pre-designed proforma which included the socio-demographic characteristics and laparoscopic findings in various abdomino-pelvic organs. The data was analyzed using SPSS software version 16 (SPSS for windows, Version 16.0 Chicago: SPSS Inc.). Results: During the study period, 24 cases of endometriosis were diagnosed out of the 490 infertile women seen. This gave the prevalence rate of 4.9 %. The mean age of the women was 30.3±4.1 years. Majority (58.3%) of the patients were of social class I. Sixteen (66.6%) patients presented with primary infertility, while 8 (33.3%) had secondary infertility and were all primiparous. Chocolate cysts were bilateral in 9 (37.5%) patients and unilateral in 6 (25.0%). Thirteen (54.2%) patients had bilateral tubal adhesions, while 5 (20.8%) had unilateral adhesions. Thirteen (54.2%) patients had bilateral patent tubes while 4 (33.3%) and 2 (16.7%) patients had unilateral and bilateral tubal blockade respectively on dye test. Seventeen (65.4%) patients had adhesions at the cul-de-sac while eight (33.3%) patients had involvement of bowel to adhesion. Conclusion: Endometriosis is an important common gynaecological problem among infertile women seen at laparoscopy. Majority of infertile women with endometriosis had chocolate cysts, cul-de-sac adhesion and bilateral patent tubes at laparoscopy and dye test.